"I must be mad to watch this lot" :a qualitative study examining the effect that supporting a small, local football club has on the mental health of supporters - Pringle, Alan (2008)
This study examines the effect that supporting a football team and attending their matches can have on the mental health of the supporters. The examination of the interplay between supporting a team and developing and maintaining some of the conditions needed to maintain good mental health is developed along three main themes.